(untitled) (Altre Modernità, 2019)
This paper investigates the first five seasons of Netflix original series Orange Is the New Black (2013-2019) through an interdisciplinary perspective that combines some critical approaches and tools from cultural studies, gender and feminist studies (primarily intersectionality), and cultural criminology. The study aims at understanding and accounting for the complex phenomenon of female violence from a different angle and devises new critical instruments to approach narratives of women who commit crimes that challenge deeply ingrained stereotypes and frame the possibility and construction of criminal women’s agency